An Unusual Subcutaneous Mass in an Otherwise Healthy Patient: A Case Report of Localized Histoplasmosis Diagnosed on Excisional Biopsy - Brendon M. Esquibel; Christine J. Waller; William A. Agger (Case Reports in Infectious Diseases)
Patients are commonly referred to general surgery clinics for evaluation of soft-tissue masses of the trunk and extremities. The primary goal of surgical referral is to confirm the presence of a mass, to assess the need for additional imaging and/or testing, and to gauge amenability to surgical biopsy, whether incisional or excisional. This is a case of a 67-year-old woman who was referred to surgery clinic for a small soft-tissue mass near her left elbow that had increased in size and pain over the past year. The mass had been present for several years. After MRI imaging revealed a nonspecific process, an excisional biopsy was performed. Following a careful review of the patient’s history, risk factors, and histological results, a diagnosis of localized subcutaneous Histoplasma capsulatum var. capsulatum infection was made. Without signs or symptoms of active, systemic disease, no further treatment was recommended. The patient was provided risk factor counseling for symptoms or signs of active histoplasmosis and outpatient follow-up. Histologically, most masses will return as benign and mesenchymal in origin. However, soft-tissue masses may arise from uncommon etiologies and a broad differential is needed to ensure appropriate management and recommendations.